TRAINING NEEDS FOR DISTANCE LEARNING PACKAGES VIA SOCIAL MEDIA ON ACADEMIC LEADERSHIP FOR THE 21 ST CENTURY OF SCHOOL ADMINISTRATORS UNDER NONTHABURI PRIMARY EDUCATION SERVICE AREA OFFICE, THAILAND - Tuntirojanawong, Suttiwan (PEOPLE: International Journal of Social Sciences, 2018)
The purposes of this research were (1) to study training needs for distance learning packages via social media on academic leadership for the 21 st century of school administrators under Nonthaburi Primary Education Service Area Office. (2) to compare training needs for distance learning packages via social media on academic leadership for the 21st century of school administrators, as classified by school size. The sample consisted of 127 administrators in school under Nonthaburi Primary Education Service Area Office. The research instrument was a rating scale questionnaire with .97 level of reliability. The statistics used for data analysis were percentage, mean, standard deviation, and one-way analysis of variance. The findings revealed that (1) both the overall and by-aspect training needs for distance learning packages via social media on academic leadership for the 21stcentury of school administrators under Nonthaburi Primary Education Service Area Office were rated at the highest level ; aspects of training needs for distance learning packages via social media on academic leadership for the 21st century could be ranked as follow : encouraging concern for achievement, managing instructional resources, developing academic climate, and coordinate instructional program; and (2) no significant difference was found regarding the overall training needs for distance learning packages via social media on academic leadership for the 21stcentury levels of the administrators of schools with different sizes in Nonthaburi Primary Education Service Area Office.